Experimental research of the chained form manipulator - Chung, Woojin; Nakamura, Yoshihiko (IEEE International Conference on Intelligent Robots and Systems, 1998)
Exploiting unique features of nonholonomic systems, innovative and advantageous mechanisms can be designed. We have proposed the chained form manipulator which is a controllable n-joint manipulator with only two actuators. The chained form manipulator is designed not only to satisfy chained form convertibility, but also to achieve control simplicity. Design requirements and mechanical design of the chained form manipulator were proposed in our prior work. For the experimental verifications, we fabricated a prototype. So far, various control strategies for nonholonomic systems have been proposed. In this paper, an efficient motion planning scheme for the chained form is presented to approximate any holonomic path with the feasible nonholonomic path. Furthermore, a new concept of motion planning is proposed through the analyses of the initial-condition sensitivity. Combining these two approaches, the motion planning scheme is constructed towards practical applications. Presented experimental results show the usefulness of the design and the applied control scheme.